Adaptive reactive power control for voltage rise mitigation on distribution network with high photovoltaic penetration - alwez, Mustafa Abo; Jasni, Jasronita; MohdRadzi, Mohd Amran; Azis, Norhafiz (Elsevier Ltd, 2025)
This research addresses the challenge of voltage rise on low voltage distribution networks with high photovoltaic penetration. The proliferation of distributed generators, particularly small-scale PV systems, has raised concerns about voltage stability and power quality in these networks. Existing reactive power control techniques, such as fixed power factor and voltage-based methods (Q(V)), have limitations in effectively mitigating voltage rise while considering load variations and network sensitivity. To overcome these limitations, an adaptive reactive power control technique is proposed in this research. The technique combines both PV active power injection and network voltage considerations in real-time to dynamically adjust reactive power output. Unlike traditional methods, which directly link reactive power reference to PV active power or voltage, the adaptive technique calculates the change in reactive power reference (ΔQ) based on both factors. This dynamic approach enables more responsive and accurate voltage regulation. The effectiveness of the adaptive technique is demonstrated through MATLAB simulations on a representative low voltage distribution network. The results show that the adaptive technique outperforms existing methods, providing better voltage regulation and reduced losses. The technique's adaptability to different scenarios and variations is also highlighted. However, it is noted that the adaptive technique may have a slightly slower response time compared to existing methods due to its dynamic nature.